Influência do corte a gás nas propriedades mecânicas do aço API 5L X-70 proveniente do resfriamento acelerado - Cleydson Fernando Gomes Torres (2013)
This work was developed looking for to understand and improve the cutting process and preparation of samples sent to Usiminas mechanical tests laboratory, with regard to the influence of gas cutting on the mechanical properties of API 5L X-70 steel produced by accelerated cooling process. To understand this process tensile, hardness and metallographic analyses in steels was carried out. It was analyzed the heat affected zone (HAZ) by gas cutting and checked how it can change the mechanical properties of steel. The results obtained establish the best parameters for cutting and preparing the specimens to ensure that these parameters do not affect the results of the mechanical properties of the steel.